The Roles of Virtual Reality and Augmented Reality During The COVID-19 Pandemic - Yuliana Yuliana (Unversitas Muhammadiyah Mataram, 2021)
Abstract: This paper aims to describe the roles of virtual reality and augmented reality during the COVID-19 pandemic. Method of the study: It is a narrative literature review. Literature was searched in Science Direct and Google Scholar databases. Review and research paper were included. Short notes and commentary were excluded. Results revealed that the invention of Augmented-Reality, Virtual-Reality, and Mixed-Reality technologies gives integrations of virtual and physical objects. Those technologies have many usages in education, experiments, manufacture, and business. Users can have hybrid experiences because the combination of the interactive physical and virtual connections. In business, the interested customers will buy the products. In education, these technologies will help the students in learning process. In healthcare, it can be done to do simulation for preventing the COVID-19 pandemic. In conclusion, the roles of augmented reality and virtual reality are very essential, such as in health, education, business, manufacture, and experiments.Abstrak: Tulisan ini bertujuan untuk mendeskripsikan peran virtual reality dan augmented reality selama pandemi COVID-19. Metode penelitian adalah tinjauan literatur naratif. Literatur dicari di database Science Direct dan Google Scholar. Review dan makalah penelitian merupakan kriteria inklusi. Catatan pendek dan komentar diekslusikan. Hasil penelitian mengungkapkan bahwa penemuan teknologi Augmented-Reality, Virtual-Reality, dan Mixed-Reality memberikan integrasi objek virtual dan fisik. Teknologi tersebut memiliki banyak kegunaan dalam pendidikan, eksperimen, manufaktur, dan bisnis. Pengguna dapat memiliki pengalaman hybrid karena kombinasi koneksi fisik dan virtual interaktif. Dalam bisnis, pelanggan yang tertarik akan membeli produk. Dalam dunia pendidikan, teknologi ini akan membantu siswa dalam proses belajar. Di bidang kesehatan, bisa dilakukan simulasi pencegahan pandemi COVID-19. Hasil penelitian menunjukkan bahwa peran augmented reality dan virtual reality sangat penting, seperti dalam kesehatan, pendidikan, bisnis, manufaktur, dan eksperimen.